Identifikasi Gaya Belajar Anak Usia Dini melalui Pendekatan Deskriptif di TK Gugus I Kecamatan Cipedes Kota Tasikmalaya - Dwi Putri, Aulia; Rahman, Taopik; Respati, Resa (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to describe the learning styles of 4–5 year old children in Kindergarten Cluster I, Cipedes District, based on the VAK (Visual, Auditory, and Kinesthetic) model. Understanding children's learning style tendencies is crucial to support a learning process that aligns with the developmental characteristics of early childhood. This study used a quantitative approach with descriptive methods. The research sample consisted of 123 children aged 4–5 years selected using a random sampling technique. Data were collected through observation questionnaires completed by 12 class teachers, and analyzed using descriptive statistics with the help of SPSS and Microsoft Excel. The results showed that most children had visual and kinesthetic learning styles in the high category, each with 99 children (80.5%). Auditory learning styles were also quite high, with 78 children (63.4%), while no children were in the low category for all three types of learning styles. These findings indicate that visual and kinesthetic learning styles are more dominant than auditory in children aged 4–5 years at the research location. These findings demonstrate the importance of teachers understanding children's learning style tendencies to design appropriate learning. This research provides practical contributions for early childhood education teachers in designing varied activities that address all learning styles. Its novelty lies in the quantitative mapping of early childhood learning styles at the local level as a basis for data-driven learning planning